Hydrothermal Synthesis of Activated Carbon/α-Fe2O3 Nanocomposite and Its Application for Removing Tartrazine Dye. Issue 1 (March 2020) - Lubis, S; Ramli, M; Sheilatina; Ermanda, Y
Abstract: Hematite containing activated carbon (AC/α-Fe2 O3 ) nanocomposite has been prepared by hydrothermal method and used as photocatalyst for removing tartrazine dye. Hematite was extracted from iron sand while activated carbon was derived from coffee waste which was activated using hydrochloric acid. The structure and morphology of photocatalyst was characterized by means of X-ray diffraction (XRD), nitrogen adsorption-desorption (BET) and Scanning Electron Microscopy-Energy-Dispersive X-Ray Spectroscopy (SEM-EDS). These techniques indicate that the AC/α-Fe2 O3 nanocomposite has an average crystallite size of 35.47 nm and specific surface area of 41.52 m 2 /g. The photocatalytic activity evaluation showed that various factors influencing the removal of tartrazine dye including pH of dye solution, photocatalyst dosage, dye concentration and irradiation time. The results showed that AC/α-Fe2 O3 nanocomposite can remove tartrazine up to 91.01% under UV light and 93.69% under solar light which were obtained at pH value of 2, photocatalyst dosage of 250 mg and initial concentration of tartrazine is 15 ppm with irradiation time for 210 min under UV light and 180 min under solar light. The AC/α-Fe2 O3 nanocomposite also can remove tartrazine dye contained in noodle waste water up to 94.67% and 97.86 under UV light irradiation for 150 min and 120 min under solar light irradiation, respectively.